Energy in the Caspian Region Present and Future - Kalyuzhnova, Yelena; Jaffe, Amy Myers; Lynch, Dov; Sickles, Robin C. (Palgrave Macmillan UK, 2002)
The energy reserves of the Caspian Region have been hailed as the new 'Middle East'. This book offers a thorough assessment of its energy resources and the nature of the international politics that surround them. This volume presents a unique study of the various dimensions of Caspian energy, ranging from the geopolitical to the economic, technical, religious and political